Comparison of the effects of anthropogenic seismic events and natural earthquakes on buried infrastructure network components - Rusek, Janusz; Słowik, Leszek; Tajduś, Krzysztof (Bulletin of the Polish Academy of Sciences Technical Sciences, 2023)
Mining tremors may have an impact on the safety risk of steel pipelines through their effects. It is therefore important to quantify the impact of a high-energy mining tremor in terms of strength. In addition, a comparison of the results obtained with the effect of a seismic tremor can illustrate the scale of such a hazard. Recently, this has been a very frequently raised issue in the area of surface protection against negative mining impacts and the protection of post-mining areas. Ensuring safe use is particularly important for gas transmission elements. This paper presents the results of a comparative analysis of the impact of mining tremors and seismic impacts on a specimen steel pipeline segment. The analyzed pipeline is located in the eastern part of Poland in the area of paraseismic impacts of the LGCD (Legnica-Glogow Copper District) mine. For this purpose, an analytical approach was used to assess the impact of seismic wave propagation on underground linear infrastructure facilities. Accelerogram records for the 02-06-2023 seismic tremor from Turkey and the mining tremor for 11-25-2020 were used. In the case of the design of underground pipelines, the cross-section of the element for which measures describing wall stress and the ovalization of the cross-section are determined is usually considered. In the situation of the influence of seismic wave propagation or so-called permanent ground deformation, the response of the pipeline in the longitudinal direction is analyzed. As a final result, longitudinal strains transferred to the pipeline as a consequence of the propagating seismic wave and mining tremor were determined. The absolute difference between the deformations in the ground and along the length of the pipeline was determined. This type of analysis has not been carried out before and provides new insights into the topic of paraseismic impacts on the scale of their interaction with natural earthquakes. Mining tremor data was obtained from the mine’s seismological department. The seismic tremor data, on the other hand, was downloaded via the publicly available ESM (Engineering Strong- Motion Database).